ASEAN States Cooperation in the Control and Prevention of Illicit Drugs Trafficking - Sinar Aju Wulandari; Putri Kirana (Universitas Airlangga, 2023)
The high modus operandi and increasing technological sophistication have implicate the transnational movement of illicit drug trafficking. The phenomenon of increased narcotics crime cases poses a threat to countries, including those in the ASEAN region. This type of crime poses a threat to the production and trade of illegal drugs. ASEAN, as a regional organization in Southeast Asia, is still facing several challenges, particularly the commitment of its member countries to combating illicit drug trafficking. Aside from funding issues, geographical location, cultural challenges, and social customs are all factors influencing the speed with which narcotics are handled. Several programs were initiated by each country in the ASEAN region with the primary goal of collaborating to reduce narcotics distribution and abuse. This article aims to analyze the sustainability of the ASEAN 2015 Drug-Free Program and the role of UNODC in the ASEAN region. The normative legal research method was used in this article, with primary and secondary legal sources. The article concludes that the program for dealing with narcotics crime begins with the ASEAN drug-free declaration, which harmonizes member countries' perspectives through their representatives to eliminate the cultivation, consumption, and trade of narcotics across national borders. As an international organization, UNODC (United Nations Office on Crime and Drugs) exists to facilitate cooperation and coordination through programs initiated with special narcotics agencies from each member country. Coordination between the two organizations is critical for the successful implementation of the program that has been initiated.